ANALISIS TINGKAT KINERJA GURU TETAP YAYASAN DAN GURU TIDAK TETAP DI SMK SWASTA SE-KOTA MALANG - Halim, Lidia; Firmana, Mochamad Sheisar (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
This study is based on the differences in rights received from permanent teacher and non-permanent teacher, such like teaching hours, benefits received, certification rights from government, and other incentives. So based on the background, the purpose of this research to identify and analyze differences in performance level of permanent teachers and non-permanent teachers at The Private Vocational High School in Malang City. The population on this research is all of Private Vocational High School in Malang City which amounted to 40 schools. The sample of this research is 10 schools, which each school will be represented by 5 permanent teachers and 5 non-permanent teachers. The total of each sample are 50 permanent teachers and 50 non-permanent teachers. This research uses questionnaire and quick interview method. This research’s data analysis is Chi-square statistics. The results showed that there was no difference in performance between permanent teacher and non-permanent teacher on Private Vocational High School in Malang City.